The Role of Traditional Public Buildings in Shaping Rural Architecture - Omonova Dilnoza Fayziddinovna; Ubaydullayeva Dildora Fayziddinovna (Genius Journals, 2023)
This article is a study of the organization of a network of public buildings in rural areas and the changes that have taken place in modern Uzbek architecture. The article discusses the types of public buildings, their functions, analyzes the location of public buildings in rural areas, and describes the role of public buildings in shaping the social and cultural environment in the village. In addition, the article touches upon the problems associated with the preservation of traditional public buildings and their functions in modern architecture. The results of the study can be useful for architects, designers and anyone interested in the preservation and development of the national architectural culture
Keywords: rural architecture; urbanization; public buildings